Valuation of the impact of celestial bodies on the equipotential surface of the Earth’s gravity field - Petroškevičius, Petras; Popovas, Darius (Geodesy and Cartography, 2012)
The article analyzes the impact of celestial bodies on the equipotential surface of the Earth’s gravity field. It is necessary to assess impact while performing precise geodesic, gravimetric and astronomic measurements and doing research on the Earth’s shape and gravity field. The biggest impact is faced due to the closest celestial bodies such as the Moon and the Sun. Using tide generating potential revised formulas for impact evaluation of celestial bodies’ effect was derived. Valuation of the impact of celestial bodies was derived by using revised formulas of the tide generating potential. The evaluation of the effect of the Moon and the Sun on equipotential surface deformation was performed. The results of the carried out evaluation for the equipotential surface of the whole Earth’s gravity field and of Lithuanian territory in particularly are presented.Article in Lithuanian.Potvynio potencialo įtakos sunkio lauko ekvipotencialiniam paviršiui vertinimasSantrauka. Analizuojamas dangaus kūnų poveikis Žemės sunkio lauko ekvipotencialiniam paviršiui. Šį poveikį būtina įvertinti atliekant precizinius geodezinius, gravimetrinius ir astronominius matavimus, Žemės formos bei jos gravitacijos lauko tyrimus. Didžiausias poveikis sunkio laukui artimiausių Žemei dangaus kūnų – Mėnulio ir Saulės. Taikant potvynio potencialą, gautos patikslintos formulės dangaus kūnų poveikiui apskaičiuoti. Įvertinta Mėnulio ir Saulės poveikis ekviptencialiniam paviršiui. Pateikti poveikio visai Žemei ir Lietuvos teritorijai vertinimo rezultatai.Reikšminiai žodžiai: dangaus kūnų poveikis, potvynio potencialas, ekvipotencialinis paviršius.First published online: 03 Aug 2012